China's Anti-Dumping Problems and Mitigation through Regional Trade Agreements - Yanlin Sun; John Whalley (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper highlights the severity of China's AD problems, and high concentration of AD actions taken by the top initiators, noting that China can offer a higher level of economic integration in an RTA in exchange for improved regional AD provisions. Case studies on RTAs give precedents in modifying regional AD provisions. Our finding of a weak effect of existing RTAs on mitigating China's AD problems suggests that China could become more active in mitigating AD problems by RTA negotiations.
Keywords: F13; 330; anti-dumping; Regional Trade Agreement; mitigation